Conditions physico-chimiques du complexe lagunaire de Sinoe en 1973 - Boghici, Viorica (Cercetări Marine - Recherches Marines, 2026)
The author presents the physical and chemical parameters of the lagoons of Sinoe, which are to be considered for the subsequent works of pisciculture management. A special mention is made, first, of the frequent sudden variations in water salinity due to the simultaneous communication with sea and fresh waters of Razelm and, second, of the low average of salinity during the year of study as compared to the values of the last two decades.